2010
DOI: 10.1590/s1516-14392010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole release using natural rubber latex as matrix

Abstract: Natural Rubber Latex (NRL) can be used successfully in controlled release drug delivery due to their excellent matrix forming properties. Recently, NRL has shown to stimulate angiogenesis, cellular adhesion and the formation of extracellular matrix, promoting the replacement and regeneration of tissue. A dermatological delivery system comprising a topically acceptable, inert support impregnated with a metronidazole (MET) solution was developed. MET 2-(2-methyl-5-nitro-1H-imidazol-1-yl) ethanol, has been widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 22 publications
6
48
0
1
Order By: Relevance
“…We can observed that diclofenac is encapsulated in natural latex membranes, where the NRL membrane allows a gradual release of diclofenac from the aqueous solution. We observed that the release profiles for sodium diclofenac in a NRL matrix is similar from our previous work 8 , but the saturation point is different and the inclination of bi-exponential function. In this work, the points to saturation at approximately 74 hours.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…We can observed that diclofenac is encapsulated in natural latex membranes, where the NRL membrane allows a gradual release of diclofenac from the aqueous solution. We observed that the release profiles for sodium diclofenac in a NRL matrix is similar from our previous work 8 , but the saturation point is different and the inclination of bi-exponential function. In this work, the points to saturation at approximately 74 hours.…”
Section: Resultssupporting
confidence: 84%
“…Herculano et al 7,8,35 proposed a drug release system based on natural rubber latex (NRL) for the sustained and controlled delivery of metronidazole (MET), Bovine Serum Albumine (BSA) and Stryphnodendron sp extract. They concluded that the release time of MET, BSA and Stryphnodendron sp in in vitro tests were very promising for the kinetics of release.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The membranes were obtained by deposition on the petri dish as described previously 16,17,18 . The transparency of the membrane was favored by the use of room temperature.…”
Section: Preparation Of the Membranesmentioning
confidence: 99%